Boys Town [videorecording (DVD)] - Taurog, Norman, 1899-1981; Tracy, Spencer, 1900-1967; Rooney, Mickey; Hull, Henry, 1890-1977; Fenton, Leslie, 1903-1978 (Warner Home Video, 2005)
Boys Town: Story of Father Flanagan and his founding of Boys Town, a home for juvenile delinquents.